The Effect Of Baby Massage Combination Using Lavender Oil And Baby Sleep Music (Lullaby) On The Sleep Quality Of Babies Aged 6-12 Mounths In The Working Area Pmb Supianah Malang City - Rohmah, Miftakhur; Riza Tsalatsatul Mufida; Fridya Oktavianti Soliviana (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Sleep is a factor that affects the development of infants. Babies need optimal sleep time to produce developmental hormones. Poor sleep quality in infants has a negative impact such as babies becoming easily emotional, concentration and body immunity decreases. One of the therapies to improve sleep quality is to provide external stimulus in the form of baby massage therapy using lavender oil and baby sleep music (lullaby). The aim of this study was to determine the effect of a combination of baby massage using lavender oil and baby sleep music (Lullaby) on the sleep quality of infants aged 6-12 months in the working area of PMB Supianah, Malang. This study uses a quantitative research design and the research approach used is an experimental approach. The sample in this study was a portion of infants aged 6-10 months at PMB Supianah, S.Tr.Keb., Bd, Malang, with a total of 30 respondents. The sampling technique used is purposive sampling. The analysis used is paired samples t test. The research results obtained from 30 respondents most of the respondents (infants) experienced mild sleep problems, namely 25 infants (83.3%). Whereas at the time of the posttest, it was found that most of the babies did not experience problems in their sleep, namely as many as 25 babies (83.3%). Based on statistical analysis of paired samples t test , it was obtained that the value of p = 0.000 <0.05, then H0 was rejected and H1 was accepted, which means that it can be concluded that there is a combined effect of baby massage using lavender oil and baby sleep music (lullaby) on the sleep quality of infants aged 6-12 months in the working area. PMB Supianah City of Malang. With a correlation coefficient value of 0.80, which means the level of the relationship is in the strong relationship category, where the range of correlation values between 0.60-0.799 is included in the strong relationship category. The combination of baby massage using Lavender Oil and Baby Sleep Music (Lullaby) is effective in improving the sleep quality of babies aged 6-12 months. Keywords: Baby Massage, Lavender Oil, Baby Sleep Music, Sleep Quality